Cultivating National Identity through Performance - Stubbs, N. author. aut Link
XIII, 177 p.
Keywords: As outdoor entertainment venues in American cities, pleasure gardens were public spaces where people could explore what it meant to be American. Stubbs examines how these venues helped form American identity and argues the gardens allowed for the exploration of what it meant to be American through performance, both on and off the stage.